Management of mangrove forests in Johor - as part of the coastal ecosystem management - Abdul Karim, Shashiah; Abd Rahman, Yusup; Abdullah, Mohd Jinis (2004)
The state of Johor has the longest coastline in Peninsular Malaysia, and is bounded by sea in the western, eastern and southern coast. There are a total of 21,180 ha of mangrove forests in Johor, the second largest in Peninsular Malaysia after Perak. The bulk of the mangrove forests are located in the administrative districts of Pontian, Kota Tinggi and Johor Bahru. The western coast has fringing mangroves, the eastern coast is exposed and has mostly sandy shores with mangrove only found in river mouths, while the southern coast facing the Johor Strait, has two large estuaries with mangroves and small patches of narrow fringe mangroves along, parts of the remaining coastline. The Johor State Forestry Department has been managing the mangrove forests since the early 1900. However, proper management of mangrove forests only started after the Japanese Occupation in 1947. The need to manage the multiple roles of mangrove forests has changed the role of foresters from merely dealing with traditional forestry tasks. The management system has since changed to incorporate conservation aspects of mangrove forests.